Thermomyces lanuginosus lipase-catalyzed esterification of 9,10-dihydroxystearic acid and monohydric alcohol - Awang, Roila; Basri, Mahiran; Ahmad, Salmiah; Salleh, Abu Bakar (Japan Oil Chemists' Society, 2005)
An enzymatic method has been developed for the preparation of dihydroxystearic acid ester in high conversion (∼90%) by esterification of 9,10-dihydroxystearic acid and 1-octanol at moderate temperature (50 °C) using immobilized lipase from Thermomyces lanuginosus (Lipozyme TL IM) as biocatalyst. The effects of enzyme dosage, reaction temperature, reaction time and reusability of the enzyme in esterification were studied.